2019
DOI: 10.1111/ejn.14329
|View full text |Cite
|
Sign up to set email alerts
|

Weighting of neural prediction error by rhythmic complexity: A predictive coding account using mismatch negativity

Abstract: The human brain's ability to extract and encode temporal regularities and to predict the timing of upcoming events is critical for music and speech perception. This work addresses how these mechanisms deal with different levels of temporal complexity, here the number of distinct durations in rhythmic patterns. We use electroencephalography (EEG) to relate the mismatch negativity (MMN), a proxy of neural prediction error, to a measure of information content of rhythmic sequences, the Shannon entropy. Within eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
56
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(77 citation statements)
references
References 69 publications
21
56
0
Order By: Relevance
“…They are also in agreement with studies that found differences in sustained tonic activity-as opposed to phasic responses such as the MMN-when comparing low-and high-entropy contexts (Auksztulewicz et al, 2017;Barascud et al, 2016;Nastase, Iacovella, & Hasson, 2014;Overath et al, 2007). Closer to assessing the effect of precision in a musical context, recent research shows that the entropy of short rhythmic sequences modulates MMN responses (Lumaca, Haumann, Brattico, Grube, & Vuust, 2019). However, in this study rhythms were presented as repeated short patterns, which makes them less akin to actual musical stimuli than our HE sequences.…”
Section: Discussionsupporting
confidence: 88%
“…They are also in agreement with studies that found differences in sustained tonic activity-as opposed to phasic responses such as the MMN-when comparing low-and high-entropy contexts (Auksztulewicz et al, 2017;Barascud et al, 2016;Nastase, Iacovella, & Hasson, 2014;Overath et al, 2007). Closer to assessing the effect of precision in a musical context, recent research shows that the entropy of short rhythmic sequences modulates MMN responses (Lumaca, Haumann, Brattico, Grube, & Vuust, 2019). However, in this study rhythms were presented as repeated short patterns, which makes them less akin to actual musical stimuli than our HE sequences.…”
Section: Discussionsupporting
confidence: 88%
“…Despite these limitations, our work provides further evidence for the effect of uncertainty-or precisionon prediction error, which is consistent with an increasing number of empirical findings (Garrido et al, 2013;Hsu et al, 2015;Lumaca et al, 2019;Sedley et al, 2016;Sohoglu & Chait, 2016;Southwell & Chait, 2018), theories of predictive processing and models of music perception (Clark, 2016;Feldman & Friston, 2010;Hohwy, 2013;Ross & Hansen, 2016;Vuust et al, 2018). Furthermore, our findings confirm that MMNm responses can be reliably recorded in realistic paradigms where sounds constantly change, which constitutes a methodological improvement on existing approaches.…”
Section: Limitations and Future Directionssupporting
confidence: 88%
“…The ensuing precision-weighted prediction error would ensure that primarily reliable sensory signals drive learning and behavior. While a growing body of research already provides evidence for this phenomenon in the auditory modality (Garrido, Sahani, & Dolan, 2013;Hsu, Bars, Hämäläinen, & Waszak, 2015;Lumaca, Haumann, Brattico, Grube, & Vuust, 2019;Sedley et al, 2016;Sohoglu & Chait, 2016;Southwell & Chait, 2018), our study was the first to show its presence in a more ecologically valid setting such as music listening. Furthermore, the findings also pointed to a feature-selective effect in which only prediction error responses related to the manipulated auditory feature-pitch, in our case-are modulated by uncertainty.…”
Section: Introductionmentioning
confidence: 69%
“…These theoretical views of the brain have already succeeded in providing new and testable hypotheses, leading to new or revisited experimental paradigms to address how the brain adapts under uncertainty [6][7][8][9][10] . A striking example is the growing interest in how stimulus predictability modulates some long-established sensory responses [11][12][13] . However, beyond the great insights that those theories have already provided, the precise mental processes and neurophysiological mechanisms that subsume perceptual learning remain elusive.…”
Section: Introductionmentioning
confidence: 99%